ANALISIS KEBIJAKAN TENTANG PENYELENGGARAAN SEKOLAH/MADRASAH BERTARAF INTERNASIONAL (SMBI) - Walid, Muhammad (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2010)
This article tries to discuss policy of international school that is the government's efforts to improve the quality of Indonesian education for belonging competitiveness among an others countries in the global era. One of them adopts international standards of OECD members as a key factor in addition as well as uses national education standards. In practice, international school policy starts to look some weaknesses, both conceptual and learning system. Like proverb says ‘there is no ivory that is not cracked’, so the government should perform various steps to improve the concept of international school by involving the various elements of education stakeholders and conduct in-depth research before the policy is decided.Key word: School, Madrasah, International